Tingkat Kepuasan Pasien Pengguna Sistem Pendaftaran Rawat Jalan Berbasis Online Menggunakan Metode EUCS di Rumah Sakit Nur Hidayah Bantul Yogyakarta - Sulistiana, Etika; Purbobinuko, Zakharias Kurnia; Dewi, Tika Sari (Jurnal Indonesia Sehat, 2024)
Background: The online registration system at Nur Hidayah Hospital Bantul still finds problems related to application errors, there are problems when uploading KTPs for registering new patients, and at Nur Hidayah Hospital Bantul there has not been a satisfaction survey of users of the online-based outpatient registration system. Objectives: To determine the description of patient satisfaction using the online-based outpatient registration system using the EUCS (End User Computing Satisfaction) method. Research method: this research is quantitative descriptive research using a cross-sectional approach. The tool used to collect primary data in this research was the EUCS questionnaire. The sample in this study amounted to 96 accidental sampling. Research Results: the results of the descriptive analysis showed that the majority of respondents were satisfied. The results of the univariate analysis regarding the satisfaction of patients using the online-based outpatient registration system have the majority of satisfaction index interpretation scores that fall into the range of 61-80% in the satisfied category. Conclusion: online registration has a high level of satisfaction in terms of Content, Accuracy, Format, Ease of Use and Timeliness. The recommended suggestion is for developers to pay more attention to the format and reports produced by the online registration system so that they are easier to understand and comprehend.